IDEOLOGI POLA HIAS GAYA KANGKANG DI BALI - Rema, I Nyoman (PANGKAJA, 2012)
Decorative patterns straddle style is a culture of the past, which was once owned by the ancestors of Bali, in prehistoric times, engraved on the megalithic buildings, such as the sarcophagus, and others. The creation of decorative pattern is based on the belief in ancestral spirits, and then evolved into a more complex form and ideology, when the arrival of Hindu influence. This study only presents the single issue, in relation to human ideology decorative patterns straddle style in prehistoric times until the arrival of Hindu influence in Bali. This study used two theories are theories and religious symbols, given the data in the form of archaeological artifacts left behind decorative patterns straddle style, contains an idea, concept, belief in ancestral spirits, supernatural powers and developing worship ancestors who worshiped together with the gods. This research is a qualitative study, using the method of observation and study literature, arkeologireligi approach. Data analysis conducted descriptive-qualitative process; reduction, data presentation, draw conclusions. In the final stage after the data analysis, data presentation made in accordance with the proposed issue. So it can be seen that in prehistoric times the creation of human-style decorative patterns straddle motivated by belief in ancestral spirits, magical powers, and determine the efficacy, safety, and peace. At the time of the entry of Hindu culture to this day, worship of ancestors, acculturated to the worship of the gods together, known as Acintya. Keywords: ideological, confidence, style crotch, ancestors, Acintya